Pengaruh Celebrity Endorse dan Kualitas Informasi terhadap Keputusan Pembelian dengan Kepercayaan Sebagai Variabel Intervening pada Online Shop - Tragandi, Rossidin; Syamsarina, Syamsarina; Sarmigi, Elex; Mailindra, Wiyan (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to determine the effect of celebrity endorse and information quality on purchase decision mediated by customer trust among tiktok shop users in Siulak Mukai. The sample of this research was 260 respondents. Data was collected using a questionnaire that had been tested for validity and reliability. The data analysis technique used is descriptive analysis using SEM Amos 22. The results of the research show that there is a significant direct influence between celebrity Endorse and information quality on customer trust and purchase decision among tiktok shop users. There is a partial influence of the mediating impact of customer trust between celebrity endorse and information quality on purchase decision on tiktok shop users. This shows that customer trust can be built through good celebrity endorsers and quality information so that customers use online platforms to find their needs and desires and do not switch to other competitors.